Decrease in sodium density observed during auroral particle precipitation over Tromsø, Norway. Issue 17 (6th September 2013) - Tsuda, T. T.; Nozawa, S.; Kawahara, T. D.; Kawabata, T.; Saito, N.; Wada, S.; Ogawa, Y.; Oyama, S.; Hall, C. M.; Tsutsumi, M.; Ejiri, M. K.; Suzuki, S.; et al.
<x xml:space="preserve">Abstract</x> [1] Using a simultaneous and common‐volume observation by a European incoherent scatter (EISCAT) VHF radar and a sodium lidar at Tromsø, Norway (69.6°N, 19.2°E), we have determined, for the first time, the effect of pure particle precipitation, excluding that of the electric field, on sodium density variations. Our observation on 24–25 January 2012 showed that sodium atom density decreased when there was no ion temperature enhancement (indicating a weak electric field) and the electron density increased (indicating strong particle precipitation). From the results, we have concluded that auroral particle precipitation induced sodium atom density decrease in this event. Furthermore, a discussion is provided regarding the time response of the decrease in sodium density.